2010
DOI: 10.2147/ijn.s13629
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of carboxylated multiwall nanotubes with imidazole derivatives and their toxicity investigations

Abstract: Imidazoles and their derivatives are compounds with chemotherapeutic applications. In this study, we investigated the chemical functionalization of carboxylated multiwalled carbon nanotubes (MWNT–COOH) by 1,2-phenylendiamine. Multiwalled nanotube (MWNT)–benzimidazole was obtained by an MWNT–amide reaction with POCl3 after 72 hours, which was confirmed by Fourier transform infrared, scanning electron microscopy, thermal gravimetric analysis, and elemental analysis. These functionalizations were chosen due to -N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Also, it can be due to a smaller diameter of pristine MWCNT NM403 and amino-MWCNT NRCWE-049 compared to the one of carboxyl-MWCNT NRCWE-042 [42]. For amino functionalization, studies have demonstrated no significant variation in toxicity in comparison to the pristine CNT form [21]. Also, a study by Loos et al [43] demonstrated enhanced CNT associated toxicity when functionalized with an amino group in comparison to a carboxyl group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it can be due to a smaller diameter of pristine MWCNT NM403 and amino-MWCNT NRCWE-049 compared to the one of carboxyl-MWCNT NRCWE-042 [42]. For amino functionalization, studies have demonstrated no significant variation in toxicity in comparison to the pristine CNT form [21]. Also, a study by Loos et al [43] demonstrated enhanced CNT associated toxicity when functionalized with an amino group in comparison to a carboxyl group.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the possible relevance of CNT amino functionalizing is characterized worse. To date, it has been reported that there is no difference in cytotoxicity induced in fibroblasts between amino functionalized and pristine CNT [21]. There might even be a mitigation of the toxicity induced by pristine CNT Raw264.7 macrophages and PC12 cells [22].…”
Section: Introductionmentioning
confidence: 97%
“…Bands at 1633 cm −1 and 1495 cm −1 (corresponding to amide group, − CO-NH-I and II) and for terminal amine at 3400 cm −1 are observed. [23][24][25]32 Figure 2 depicts XPS partial spectra at the C 1 s region of various functionalized carbon nanotubes, where new spectral contributions are appreciable close to the band centered at around 285 eV; this indicates the presence of different types of carbon over the carbon nanotube surface. The presence of the band centered at 284.9 eV indicates the presence of the typical carboncarbon C─C bond.…”
Section: Ftir and Xps Resultsmentioning
confidence: 99%
“…The obtained black solid was vacuum-dried at 80 °C during 24 hours. 24 To disperse CNTs-G0, 50 mg of CNTs-G0 in 50 mL of methanol were placed in a round flask of 100 mL and sonicated for 10 min at room temperature. 4 mL of methyl acrylate were added dropwise during 30 min at 0 °C.…”
Section: Functionalization Of Carbon Nanotubesmentioning
confidence: 99%
“…A good approximation with the exact solution of the equations is achieved by using only a looser mesh grid. Example 2 In the second problem, we consider the 2D Burgers' equations with the following initial conditions [33] u(x, y, 0) = x + y, v(x, y, 0) = x − y, and the computational domain has been taken as D = {(x, y) : 0 ≤ x ≤ 0.5, 0 ≤ y ≤ 0.5}. The exact solutions are as follows:…”
Section: Solving 2d Burgers' Equationsmentioning
confidence: 99%